Harnessing the Public Health Power of Model Codes to Increase Drinking Water Access in Schools and Childcare. (2015) - Wilking, Cara L.; Cradock, Angie L.; Gortmaker, Steven L.
Abstract : Drinking water is an important health behavior to support overall child health. Research indicates that children are consuming too little water and too many sugary drinks. Overconsumption of sugary drinks increases child risk for the epidemics of obesity and diet-related chronic diseases like type-II diabetes, stroke, and heart disease. Increasing access to appealing, low-cost drinking water in schools and childcare where children spend much of their time supports efforts to reduce sugary drink consumption. Drinking water infrastructure is key to water access in childcare and schools. In 2012-2013, almost one-third of permanent U.S. school buildings had plumbing systems in fair or poor condition, and almost 40 percent had major renovations or repairs planned.3 Basic plumbing standards for new construction and major renovations or repairs are contained in state and local plumbing codes, and many of these codes are derived from model codes established by private organizations. This article describes the model code process and intervention points where the public health community can work to improve plumbing standards in school buildings and childcare centers.